Ectrodactyly-ectodermal dysplasia clefting syndrome (EEC syndrome) - Monika Koul; Rahul Dwivedi; Vinod Upadhyay (Journal of Oral Biology and Craniofacial Research)
Ectrodactyly-ectodermal dysplasia- clefting syndrome (also k/a. split hand- split foot malformation <SHFM>/split hand-split foot ectodermal dysplasia- cleft syndrome/ectodermal dysplasia cleft lip/cleft palate syndrome) a rare form of ectodermal dysplasia, is an autosomal dominant disorder inherited as a genetic trait and characterized by a triad of (i) ectrodactyly, (ii) ectodermal dysplasia and, (iii) & facial clefts.